1993
DOI: 10.1002/mrc.1260310405
|View full text |Cite
|
Sign up to set email alerts
|

NMR and molecular mechanics studies on the solution‐state conformation of (−)‐scopolamine free base

Abstract: The NMR parameters of (-)-scopolamine free base in CDCl, determined by Sarazin et al. were used to reevaluate some of the stereochemicai conciusions recently reported by the authors. Similarly to the case with the protonated salt, the major contributor to the fast exchange ümit time-averaged sbucture of the free base bopate ester moiety appears to be the rotamer in which the phenyi and hydroxyl group are antipenplanar. Long-range heterondear coupling constants for the carboxyl carbon and also for the aromatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…1). The carbon numbering of atropine followed that of Glaser (1993) and it was in agreement with Leete et al ., (1975). The chemical shift assignment of aromatic carbons C13 and C14 was achieved using lanthanide shift reagents (LSR).…”
Section: Resultssupporting
confidence: 90%
“…1). The carbon numbering of atropine followed that of Glaser (1993) and it was in agreement with Leete et al ., (1975). The chemical shift assignment of aromatic carbons C13 and C14 was achieved using lanthanide shift reagents (LSR).…”
Section: Resultssupporting
confidence: 90%
“…There is a significant number of NMR investigations in the literature addressing scopolamine structure (26–42) that permit direct comparisons between our measured NMR parameters and previously published values. We have made several such comparisons for our chemical shift and J H,H measurements, and have presented them in table form.…”
Section: Resultsmentioning
confidence: 99%
“…13C NMR spectroscopy unequivocally showed that the appropriate equatorial N-methyl diastereomers were the predominant contributors to the time-averaged spectral parameters for solutions of both alkaloid free bases [12]. The four crystallographically found archetypical conformations for scopolamine free base have recently been discussed by Glaser [15].The finding of different relative stabilities of scopolamine equatorial and axial N-methyl diastereomers in various solvents or as a function of nitrogen protonation provided the impetus to undertake the ab initio calculations described below. …”
mentioning
confidence: 96%
“…Ethano-bridged free base models 14,15 [equatorial N-methyl 14 calculated to be 1.120 kcal/mol lower than axial N-methyl 15, --~ ~(eqMe) versus 101.3 ~ e~(axMe), and 103.9 ~ ~(eqMe) versus --~ ~(axMe); lone pair position not determined]. The corresponding two O-formyltropine N-methyl diastereomeric free base models (14,15) were also studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation